Resolving the observe zone: validation of the ESC 0/3-hour and the APACE criteria for NSTEMI triage - Christian Müller; Norbert Frey; Moritz Biener; Evangelos Giannitsis; Pedro Lopez-Ayala; Christoph Reich; Mustafa Yildirim; Christian Salbach (Open Heart)
Background High-sensitivity cardiac troponin tests have enhanced early myocardial infarction diagnosis, yet many patients still land in the observe zone (OZ). Guidelines suggest a 3-hour troponin measurement for those in the European Society of Cardiology (ESC) 0/1 hour-algorithm’s OZ, but evidence on extended troponin testing times and their impact on diagnostic accuracy and outcomes remains sparse.Methods Patients with suspected acute coronary syndrome were consecutively enrolled in a single-centre observational study. The triage protocol allowed an optional third troponin measurement at 3 hours or later to evaluate the performance and safety of two validated triage algorithms used to resolve the OZ.Results Of the 4605 patients, 948 were triaged to the OZ (20.6%). The prevalence of non-ST-segment elevation myocardial infarction (NSTEMI) within the OZ was 7.2%. 212 patients (22.3% of OZ patients) had a third troponin measurement and were included in the comparative analysis. For diagnosing NSTEMI, the ESC 0/3-hour criteria showed lower sensitivity (69.4%) than the criteria defined in the Advantageous Predictors of Acute Coronary Syndromes Evaluation (APACE) study (86.1%, p=0.053), with both having high negative predictive value (93.5% vs 87.5%, p=0.339). By definition, the ESC 0/3-hour algorithm categorises all patients into rule-in or rule-out, eliminating the need for an OZ, whereas 55.6% of patients remained in the OZ with the APACE criteria. Mortality rates in the OZ were similar across different timing protocols, with 30-day rates of 0.78% for third blood draws within 210 min (n=128) and 1.19% for those over 210 min (n=84); 3-year rates were 5.51% and 4.82%, confirming the safety of extended sampling.Conclusions Although the ESC 0/3-hour criteria have a lower sensitivity than the APACE criteria, it is by definition more effective because it does not leave patients in the OZ. Extending the timing for the third troponin measurement beyond 3 hours proves to be effective and safe, supporting its implementation in clinical practice.Trial registration number NCT03111862.